(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In female Mastacembelus armatus, nutritional and energy quality in form of protein glycogen and fat, along with the moisture content of tissues, liver and ovary, have been studied in relation to the menstrual cycle. In the muscle and liver, the material of protein glycogen and lipid have been recorded maximum in the resting phase compared to the other phase. In the spawning process, they were located high in ovary relative to the other process. Similarly, the muscle and liver energy content were also found high in the rest phase. In the spawning season, the energy content of ovaries was found to be highest in comparison with the other reproductive phases. There is a decline in muscle and liver nutrients in the spawning phase, which can be attributed to less feeding and a diversion of body reservoirs into gonad development during the spawning phase.